Community Empowerment in Coastal Community: A Case Study of Social Forestry in North Sumatra, Indonesia - Tampubolon, Longgak Arianto (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
Coastal community has to be empowered because of their low capacities and reliance on mangrove ecosystem. This inquiry tries to reveal the process of empowerment consisted of powerlessness, support, wish, consciousness, confidence and empowered organization. Case study is employed in this research through documentation study, in-depth interviews and direct observations. Findings show that the process cannot fully adopt existing theory. Sometimes, â€œwishâ€ precedes â€œsupportâ€. Farmer group needs to raise its wishes to reach supports. In other word, the wish is a prerequisite for the support. In addition, economic incentive and the weak enforcement of rules has become the major constraints in the process. Therefore, external interventions must be maintained continuously, and rules must be enforced properly.